Clinical and immunological characteristics of opportunistic infections in children with the natural course of HIV infection, taking into account the route of infection - V. B. Denisenko; E. M. Simovanyan (LLC "Diagnostics and Vaccines", 2022)
The purpose of the study is to improve the diagnosis and prognosis of opportunistic infections in children infected with HIV by vertical and parenteral routes, taking into account the dynamics of clinical and immunological parameters.Research methods. Clinical and laboratory examinations were carried out in 192 children infected with HIV by the vertical route (91; group I), parenteral route in infancy (44; group II) and over the age of one year (57; group III).Research results. In group I, a rapid development of immunosuppression was observed: mild immunodeficiency was diagnosed at the age of Me 4 (IQI 2-10) months, advanced immunodeficiency - Me 11 ( IQI 6-24.5) months, severe immunodeficiency - Me 23 ( IQI 11- 56) months. Clinical manifestation of opportunistic infections occurred in the first three years of life with a relatively high content of CD4-lymphocytes. Localized bacterial infections (Me 27,5; IQI 21,9-34,1/100 MYO), candidiasis (Me 14,1; IQI 10,2-18,9 / 100 MYO) and generalized infections (Me 5,2; IQI 2,9-8,5 / 100 MYO) had the highest relative incidence rate. In group II, there was a slower progression of immunosuppression (within one to seven years), the addition of opportunistic infections with a lower content of CD4-lymphocytes, in terms of one to nine years, a high relative incidence of herpes simplex infection (Me 12,9; IQI 7,8-14,9 / 100 MYO), herpes zoster (Me 3; IQI 1,5-5,4 / 100 MYO) and pneumocystosis (Me 3,8; IQI 2,1-6,4 / 100 MYO). In group III, there was a slow progression of immunosuppression (within one to eight years), the development of opportunistic infections with a low content of CD4-lymphocytes, in terms of two to ten years, a rarer manifestation of most diseases.Conclusion. These patterns should be taken into account when planning diagnostic, therapeutic and preventive measures in children with HIV infection, taking into account the path and age at the time of infection.